Educação bicha: uma a(na[l])rqueologia da diversidade sexual - Zamboni, Jésio (2016)
A series of short papers aims to build the bicha as a conceptual character, in order to be able to propose a bicha education. These papers move towards the escaping from a representational logical identity, which is tends to be hegemonic in sexual diversity movements. Gilles Deleuze’s philosophy of difference works as a holder that operates a schizo-analysis of the bicha who is approached as a becoming and as an analyzer which makes the different thinking possible. Present the bicha’s confrontation to the homosexual, gay and queer characters who are built collectively. It focuses on fighting towards the bicha during the emergency of the gay figure in Brazil at the end of the 70s. At his time, the conflict was initiated in the academicscientific plans, where the bicha concept is diminished comparing to the homosexual or even the gay, also in the political-cultural field, since the earlier organized homosexual groups started to attack the bicha as stereotype and prejudice. The route of thinking where the bicha enrolls and develops itself happens during the 80s. It is outlined in the Peter Fry’s, Néstor Perlongher’s, Herbert Daniel’s, Madame Satã’s and Waldo Motta’s work. Interferences in the concepts of sexuality and gender have been promoted. It is proposed the production of the bicha through interpellation as assemblage of misidentification. The historic production of the brazilian travesti as the prostitute bicha is discussed having the street battle for life as reference, so, they are collective sexual work territories where the travesti is forged by this kind of work. It deals with tensions and issues that constitute the travesti experience. It denies the perspective of a coherent and logical comprehension. It presents the anti-principles that define the research path. The thesis ends up on a small set of narratives that problematize the educational practices from the bicha perspective.